2016
DOI: 10.1155/2016/7841380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mg Content and Heat Treatment on the Mechanical Properties of Low Pressure Die-Cast 380 Alloy

Abstract: The present study was carried out on a 380 alloy containing 9.13% Si, 3.22% Cu, 1.01% Fe, 0.06% Mg, 0.16% Mn, and 2.28% Zn. The magnesium level was increased to 0.3 and 0.55%, by adding pure Mg to the melt. Tensile and fatigue samples were produced using low pressure die casting. The results show that the average dendrite arm spacing was about 6 μm. Increasing the amount of Mg from 0.06% to 0.55% increased the volume fraction ofπ-Al8Mg3FeSi6and Q-Al5Cu2Mg8Si6phases from 0.8% to 1.7%. Following solutionizing at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…However, the addition of magnesium caused the AlSi12 alloy to absorb much lower energy. These results are similar to the different studies reported in the previous literature (Hurtalová et al , 2013; Morin et al , 2016). It is believed that the magnesium-containing alloys absorb less energy in the tensile test and less energy in the impact test because of the brittle Mg 2 Si in their structure compared to the AlSi12 alloy.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, the addition of magnesium caused the AlSi12 alloy to absorb much lower energy. These results are similar to the different studies reported in the previous literature (Hurtalová et al , 2013; Morin et al , 2016). It is believed that the magnesium-containing alloys absorb less energy in the tensile test and less energy in the impact test because of the brittle Mg 2 Si in their structure compared to the AlSi12 alloy.…”
Section: Resultssupporting
confidence: 93%
“…With the increase of the Mg ratio, the intensity of intermetallics formed in the structure increased and China scripts were formed. Morin et al (2016) found similar secondary phases in AlSi 9 Cu 3 Fe alloy. In the literature, there are studies in which similar microstructures and components are observed on 6082 aluminum alloy (Mrówka-Nowotnik et al , 2007) and AlSi 9 Cu 3 alloy (Tillová et al , 2012).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation